Past freeze and thaw cycling in the margin of the El'gygytgyn crater deduced from a 141 m long permafrost record - G. Schwamborn; H. Meyer; L. Schirrmeister; G. Fedorov (Climate of the Past, 2014)
The continuous sediment record from Lake El'gygytgyn in the northeastern Eurasian Arctic spans the last 3.6 Ma and for much of this time permafrost dynamics and lake level changes have likely played a crucial role for sediment delivery to the lake. Changes in the ground-ice hydrochemical composition (δ 18 O, δD, pH, electrical conductivity, Na + , Mg 2+ , Ca 2+ , K + , HCO 3 - , Cl - , SO 4 - ) of a 141 m long permafrost record from the western crater plain are examined to reconstruct repeated periods of freeze and thaw at the lake edge. Stable water isotope and major ion records of ground ice in the permafrost reflect both a synsedimentary palaeo-precipitation signal preserved in the near-surface permafrost (0.0–9.1 m core depth) and a post-depositional record of thawing and refreezing in deeper layers of the core (9.1–141.0 m core depth). These lake marginal permafrost dynamics were controlled by lake level changes that episodically flooded the surfaces and induced thaw in the underlying frozen ground. During times of lake level fall these layers froze over again. At least three cycles of freeze and thaw are identified and the hydrochemical data point to a vertical and horizontal talik refreezing through time. Past permafrost thaw and freeze may have destabilised the basin slopes of Lake El'gygytgyn and this has probably promoted the release of mass movements from the lake edge to the deeper basin as known from frequently occurring turbidite layers in the lake sediment column.